The role of probiotic content of kefir in the adipogenic differentiation process of 3T3-L1 cells - Zeybek, Sabiha Gökçen; Becer, Eda; Şanlıdağ, Tamer; Yücecan, Sevinç; Vatansever, Seda (Progress in Nutrition, 2020)
Objective: Kefir is traditional fermented milk that is reported to have various health benefits such as preventing obesity. The aim of this study was to investigate the effect of kefir on lipid accumulation and cell differentiation in adipocytes. Materials and Methods: Kefir was prepared from milk and kefir powder fermentation. Then, kefir supernatant and pellet fractions were incubated for 24 h and 48 h with mature 3T3-L1 adipocytes. Cytotoxic effect of kefir on the cells was measured by MTT assay. Lipid accumulation was detected by Oil-red O staining. Anti-adipogenic activities of kefir fractions were investigated distribution of ANGPTL-4, leptin and PPAR- γ in mature 3T3-L1 adipocytes using indirect immunoperoxidase technique. Results: In the MTT assay, 0.1 mg/dl dilutions of kefir supernatant and pellet were found to be effective on adipocytes growth and differentiation after both 24 h and 48 h incubations. Lipid accumulation was reduced by both kefir supernatant and pellet in 3T3-L1 adipocytes for 24 h. As a result of immunohistochemical staining, ANGPTL-4 immunoreactivity was significantly increased in 3T3-L1 cells after treated with kefir fractions. Additionally, leptin immunoreactivity was also decreased significantly in the mature adipocytes after treated with kefir pellet. There were no differences in expression of PPAR- γ in all groups. Conclusion: Kefir fractions have prevented lipid accumulation by preserving the cell structure on 3T3-L1 adipocytes. The increased level of ANGPTL4 expression may be mediated inhibition of lipid accumulation. Moreover, kefir supernatant may play important role in preventing weight gain due to reduced leptin level.